PEDAGOGICAL CONTEXT OF "I. P. LVIV'S MEMORIES ABOUT P. G. TYCHYNA - Н. Кузьменко (Київський національний університет імені Тараса Шевченка, 2015)
The degree of studying of the problem in scientific and pedagogical literature has been researched. The importance of research in modern conditions of reforming of the educational system of Ukraine has been identified. The basic stages of Ivan Petrovych Lviv's scientific-pedagogical activity have been defined. The manuscript "I. P. Lviv's memories about P. G. Tychyna" has been analyzed to determine the main factors that influenced the formation of the personality of a famous Ukrainian poet and public figure P. G. Tychyna. The pedagogical aspect of the manuscript of "Memories..." has been studied. Pedagogical conditions of organization of educational process in the Chernigov theological seminary, in which Pavlo Tychyna studied in 1907 – 1913 have been considered. The role of the Ukrainian writer N.Kotsubynskyi, the teacher of language arts in Chernigiv theological Seminary named after V. Drozdov, and other staff of the institution in the development of literary talent of P. Tychyna has been researched.

Вивчено ступінь дослідженості проблеми у науково-педагогічній літературі. Визначено актуальність дослідження в сучасних умовах реформування освітньої системи України. Досліджено основні етапи науково-педагогічної діяльності Івана Петровича Львова. Детально вивчено та проаналізовано рукопис "Спогадів І.П.Львова про П.Г. Тичину" з метою визначення основних чинників, які вплинули на формування особистості відомого українського поета, громадського діяча П.Г. Тичини.Проаналізовано педагогічний аспект рукопису "Спогадів…". Вивчено педагогічні та побутові умови організації навчально-виховного процесу у Чернігівській духовній семінарії, в якій Павло Тичина навчався у 1907 – 1913 роках. Встановлено роль українського письменника М. Коцюбинського, учителя словесності Чернігівської духовної семінарії В. Дроздова та інших викладачів та співробітників навчального закладу у розвитку літературного таланту П. Тичини.
ПЕДАГОГІЧНИЙ КОНТЕКСТ "СПОГАДІВ І.П.ЛЬВОВА ПРО П.Г.ТИЧИНУ
Keywords: особистість; формування особистості; духовна семінарія; навчальний процес.; personality; personality development; theological seminary; the educational process.